Quantitative Sonoelastographic Assessment of the Normal Uterus Using Shear Wave Elastography: An Initial Experience. (11th May 2019) - Manchanda, Smita; Vora, Zainab; Sharma, Raju; Hari, Smriti; Das, Chandan Jyoti; Kumar, Sunesh; Kachhawa, Garima; Khan, Maroof Ahmad
Abstract : Objectives: To describe the sonoelastographic characteristics of the normal endometrium, myometrium, and cervix and to assess their variability with age and different menstrual phases. Methods: A total of 56 women were enrolled in this prospective study, who underwent transvaginal ultrasound examinations, including B‐mode imaging and shear wave elastography. The elasticity parameters (in kilopascals) of the normal endometrium, myometrium, and cervix were studied. The variability of the mean elasticity value of the endometrium in different menstrual phases and age groups was analyzed. The variability of the mean elasticity of the cervix across different age groups was also studied. Results: The mean age of the participants was 40 years (range, 25–69 years). The normal mean elasticity values ± SDs were 25.54 ± 8.56 kPa for the endometrium, 40.24 ± 8.59 kPa for the myometrium, and 18.90 ± 4.22 kPa for the cervix. A mean endometrial‐to‐myometrial elasticity ratio was calculated, which was found to be 0.65 ± 0.22. There was no significant difference in the mean endometrial elasticity values for women in different menstrual phases ( P = .176) or in different age groups ( P = .376). There was no significant difference in the mean cervical elasticity with age ( P = .192). Conclusions: Shear wave elastography is a promising adjunct to ultrasound for the evaluation of the uterus, and the results from this study may provide normal data, which may further help in diagnosing various uterine diseases.